Simbolo y metafora en la organizacion moderna: Estudio de un caso puertorriqueño - Morales Arandes, Edgardo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
In this article. I explore the relationship between symbols and human behavior in organizations. I suggest that investigators can obtain a greater understanding of an organization's social dynamics if they analyze the symbolic contents of its culture. The symbols of a multinational company's subsidiary in Puerto Rico, are analyzed in order to illustrate the scope and potential of this analytic approach. This analysis explores the relationship between such symbolic phenomena as metaphors. anecdotes and rituals and the organization's social, and political processes. Through the analysis of the changes in its symbology, I illustrate how complex factors within an organization's internal and external environment determine the relevance of a particular organizational symbology.